Diplopia Following External Dacryocystorhinostomy with Intracystic Pawar Implant Implantation: The Tale of an Unheard Complication - Deepsekhar Das; Mandeep Singh Bajaj; Swechya Neupane; Sahil Agrawal; Saloni Gupta (Delhi Journal of Ophthalmology)
Dacryocystorhinostomy (DCR) with Pawar intracystic implant placement is a simple and faster surgical option for treating epiphora. Its advantages being small length of incision(5-6mm), minimal intraoperative and postoperative bleeding, and sparing of the medial palpebral ligament with no need of creating sac and nasal mucosal flaps anastomosis. The presence of holes at upper and lower end act as extra drainage channel. This makes it superior to conventional DCR with better success rate. Herein, we report a rare complication of diplopia following implantation of Pawar’s implant. We believe in the following chain of events with anterior displacement of implant, local inflammation was evoked, resulting in subsequent scarring and medial rectus fibrosis.